Relationships Between College Students’ Control-Value Appraisals of English Learning, Achievement Emotions, and Empowerment - Wang, Jian; Zhang, Xiaohong (Universitas Islam Negeri Walisongo Semarang, 2024)
Language learning involves cognitive and non-cognitive factors. Recent research has shifted focus from cognitive outcomes to emotional factors, influenced by positive psychology and an